Host plant resistance, cultural practices and botanical pesticides four the management of bean stem maggot in small scale farmer systems - Ampofo, James Kwasi O.; Massomo, S.M.S. (International Center for Tropical Agriculture, 1995)
In our efforts to develop strategies for the manegement of bean steam maggots (bean fly) (Ophiomyia spp; Dipteras Agromyzae) in small scale farmers systems, we focus on options that are available and sustainable within the farming environment. These include host plant resistance, cultural practices and botanical pesticides. For host plant resistance, we identified varios sources of resistance from the CIAT phaseolus vulgaris core collections as well as material held in the Tanzania bean germplasm collections. Some of these sources are now in use to transfer resistence to adapted lines as well as elite breeding lines. With cultural practices, we observed previously that mulches reduced plant damage resulting from BSM attack and we set up further trials to gain a greater understanding of the mechanism of grass mulches and stabilized soil temperature at a lower level below the ambient temperature and the non-mulched treatments. This was reflected in adventitious root development and plant survival. Botanical pesticides such as aqueous extracts of neem and persian lilac seed powder and Tephrosia leaves also reduced BSM infestation and damage. These practices could be used in the development of IPM strategies for small scale farmers systems to reduce BSM pressure and increase bean yields.